Can patient reported outcomes help identify the optimal outcome in palliative surgery?. Issue 2 (16th October 2013) - Badgwell, Brian; Bruera, Eduardo; Klimberg, Suzanne V.
Abstract Background The purpose of this pilot study was to determine whether an open‐ended questionnaire captures severe symptoms in cancer patients undergoing palliative surgical consultation that a structured, validated quality‐of‐life assessment does not capture. Methods We prospectively used the Functional Assessment of Cancer Therapy–General (FACT‐G) and an open‐ended questionnaire to assess the symptoms of patients with incurable malignancies who underwent palliative surgical consultation at our institution between January 2011 and September 2012. Results Of the 69 patients enrolled, the most common indications for consultation were bowel obstruction (54%), jaundice (13%), wound problems (10%), and gastrointestinal bleeding (7%). Of the severe symptoms patients reported, 76% were identified with the FACT‐G alone, 22% were identified with the open‐ended questionnaire alone, and 2% were duplicate responses captured with both the FACT‐G and open‐ended questionnaire. The open‐ended questionnaire captured 68 instances of severe symptoms in 47 patients that the FACT‐G did not capture; of these symptoms, 52 were considered to be highly relevant to surgery and potential outcome measures. Conclusions An open‐ended questionnaire can identify severe symptoms that a global quality of life survey cannot capture and could be used in conjunction with a global survey to reassess symptoms after palliative surgical consultation. J. Surg. Oncol. 2014 109:145–150. © 2013 Wiley Periodicals, Inc.